The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1590/0104-1169.1075.2667
|View full text |Cite
|
Sign up to set email alerts
|

Universal Access to Health and Universal Health Coverage: identification of nursing research priorities in Latin America

Abstract: Objective:To estabilish a regional list for nursing research priorities in health systems and services in the Region of the Americas based on the concepts of Universal Access to Health and Universal Health Coverage. Method: five-stage consensus process: systematic review of literature; appraisal of resulting questions and topics; ranking of the items by graduate program coordinators; discussion and ranking amongst a forum of researchers and public health leaders; and consultation with the Ministries of Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 11 publications
0
20
0
11
Order By: Relevance
“…Entretanto, a comparação dos resultados com estudos atuais possibilitou verificar que não houve mudanças nas características do trabalho, com concepção de mérito. Apesar dessas limitações os achados apresentam contribuição importante em dois âmbitos: para as políticas e formação de recursos humanos de enfermagem, uma das seis categorias principais de prioridades de pesquisa em enfermagem na América Latina 28 ; e para a gestão do trabalho e educação em saúde, parte da agenda de prioridades de pesquisa em saúde no Brasil 29 .…”
Section: Discussionunclassified
“…Entretanto, a comparação dos resultados com estudos atuais possibilitou verificar que não houve mudanças nas características do trabalho, com concepção de mérito. Apesar dessas limitações os achados apresentam contribuição importante em dois âmbitos: para as políticas e formação de recursos humanos de enfermagem, uma das seis categorias principais de prioridades de pesquisa em enfermagem na América Latina 28 ; e para a gestão do trabalho e educação em saúde, parte da agenda de prioridades de pesquisa em saúde no Brasil 29 .…”
Section: Discussionunclassified
“…Delphi studies vary in terms of the sample size and type of participants, with similar studies reporting sample sizes of 18-741 participants, including staff nurses, academics and nurse clinicians (Butler et al 2009;Schoenly 2015;Sun et al 2015;Wielenga et al 2015). general, non-clinical) that identified nursing research priorities in health services and systems in the United States included academics, World Health Organization (WHO) collaborating centres and local health authorities as experts (Cassiani et al 2015). The inclusion of nursing staff in different specialties and grades and from diverse clinical settings across the UAE is congruent with similar studies and enhances the clinical relevance of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…This supports the sampling approach in this study. Although the study was regional, the identified priorities would be difficult for nurse researchers to translate into clinical research projects (Cassiani et al 2015). The modified Delphi technique contributed to the robustness of the study, especially in achieving the goal of producing clinically relevant research priorities that can be directly translated into clinical research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations